Does the work environment influence the performance of nurses at Mutiara Sukma psychiatric hospital? - Khalik, Lalu Abdul; Saimi, Saimi; Sulaiman, Lalu; Hidayati, Fitria (Journal of Midwifery and Nursing, 2024)
Study This investigate the vital role of nurses at Mutiara Sukma Mental Hospital in context service health soul. Nurse No only as provider service medical, but also plays a role important in create environment supportive work recovery patient. Nurses at RSJ have not quite enough answer to aspect physical and psychosocial, building connection therapeutic with patient, and role as bridge between patient and team interdisciplinary. Environment working at RSJ is element crucial that can be influence performance nurses and outcomes whole in maintenance soul. This study use approach quantitative with involving 110 nurses as sample. Analysis results statistics show that environment Work influential significant to performance nurse, with coefficient determination amounting to 51.5%. Discussion results study This highlighting importance environment conducive work _ in increase performance nurse. Findings This consistent with study earlier that showed connection positive between environment work and performance employee. Implications study This imply that the management of RSJ Mutiara Sukma can increase quality service health soul with focus on improvement environment work, incl facility physical, management burden work, and culture supporting organizations. In conclusion, the study This confirm that environment supportive work own impact significant positive impact on performance nurse at RSJ Mutiara Sukma. Recommendation including evaluation and improvement sustainable to factors environment Work For increase well-being nurse, confirm more service Good for patient, and supportive whole system service health soul.